ANALISIS SKALA PRODUKSI TANAMAN KOPI DI DESA PELAGA KECAMATAN PETANG KABUPATEN BADUNG - I Putu Teguh, Suryadinatha Putra1; I Ketut, Sudiana (PIRAMIDA, 2019)
The agricultural sector in Bali Province is the second priority sector in development after tourism and its position is very strategic in empowering people's economy in rural areas. Efforts to develop skills through training, adequate land area, adequate and skilled labor, and relatively low cost are essential in order to improve the welfare of the community, especially rural communities. One type of plantation that includes a smallholder plantation is a coffee plantation. Coffee is one of non-oil and gas commodities, which recently has a market that is promising in the world market. The purpose of this study is to analyze how large the influence of land area, labor, and wages both simultaneously and partially to the amount of coffee plant production in Pelaga Village Petang District Badung regency. This research was conducted on coffee farmers in Pelaga Village, Petang District, Badung Regency. The number of samples taken is 74 coffee farmers. Data collection is done through structured interviews, in-depth interviews and observation. The anaslisis technique used is multiple linear regression and production scale with Cobb-Douglas function. The result of this research stated that the area of ??land, labor, and wage have positive and significant influence both simultaneously and partially to the amount of coffee plant production in Pelaga Village, Petang District, Badung Regency. Scale production of coffee plants in Pelaga Village, Petang District Badung Regency is currently in a condition of increasing return to scale. While partially for all four independent variables in condition decreasing return to scale.